Mukhlis Knowledge Donating Towards Employee Performance - Sukamto Sukamto; Heri Poerbantoro; Rita Andini; Tri Handayani; Dwi Retna Sulistyawati (Journal Research of Social Science, Economics, and Management, 2024)
This research aims to describe how internalizing "mukhlis" Islamic values contributes to Employee Performance. Mukhlis Knowledge Contributing (MKD) is the skill of donating knowledge with the earnest intention of pleasing Allah.The concept of Mukhlis Information Donating is the contribution of genuine and relevant knowledge to enhance Employee Performance.Mukhlis Knowledge Donating is activated by one of the Organizational Learning Dimensions, specifically Team Learning and the worth of Taqorrub (getting closer to Allah).This article has consequences for the capacity of Human Resources to provide true, sincere knowledge for the benefit of the world and the hereafter, in the hope of Allah's grace.The contribution of this study to Resource-Based Theory is the function of mukhlis Islamic values in the honest donation of knowledge, as evidenced by the application of Organizational Learning aspects Team Learning and Taqorrub values.